ANTECEDENTES DEL PENSAMIENTO EDUCATIVO MUNDIAL, AMERICANO, LATINOAMERICANO Y CARIBEÑO (De la Crítica, 2023)
The following document is a critical-reflexive essay about Latin American educational thought and the different authors who have contributed to the construction of educational philosophy in Latin American countries, with special attention to the case of Venezuela. The methodology is based on a documentary review of the different texts, articles and authors that develop educational thinking from the historical perspective to the curricular praxis.